Model Pembelajaran Seni Islami dengan Pendekatan Etnopedagogi - Alistiana, Lisa; Setyawan, Dedy (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
The Islamic arts learning model holds a strategic position in the education of prospective madrasah teachers as it fosters spirituality, strengthens moral character, and bridges local wisdom with the vision of global education. This study aims to formulate an Islamic arts learning model grounded in an ethnopedagogical approach within the context of the Islamic Elementary Teacher Education Program (PGMI). Using a descriptive qualitative conceptual method, data were obtained through classroom observations, document analysis (lesson plans and teaching notes), and a comprehensive review of national and international literature. The findings indicate that Islamic arts learning in PGMI remains fragmented and tends to emphasize technical skills, with limited integration of Islamic values in the character-building process. The ethnopedagogical approach proves effective in offering contextual, participatory, and socially grounded learning experiences for students. The proposed model comprises four interrelated components: 1) Islamic values as the foundational principle, 2) participatory pedagogical strategies, 3) Islamic artistic expression as a medium for value internalization, and 4) affective–reflective assessment focusing on character formation. This study contributes to the strengthening of Islamic character education in PGMI through a holistic, applicable, and contextually relevant framework for Islamic arts learning in the 21st century.